Case report and video presentation: Trans-urethral resection of bladder endometriosis - Fadil Abid, Ammar (Urol Case Rep, 2019)
Urinary endometriosis is a rare condition accounting for 1–5.5% of the extragenital endometriosis locations. The diagnosis takes long time during which patient misdiagnosed as urinary tract infection or interstitial cystitis. A 25-year-old married woman presented with cyclical pain last for ten days every month for six months prior to diagnosis. There was no history of hematuria. Had three times caesarian section. Endometrial mass on posterior wall of bladder about 3 × 2 cm treated by transurethral resection. Chocolate appearance of blood during transurethral resection is highly suggestive of diagnosis of bladder endometriosis.